The P2X7 receptor antagonist Brilliant Blue G reduces serum human interferon-γ in a humanized mouse model of graft-versus-host disease. (24th July 2017) - Geraghty, N J; Belfiore, L; Ly, D; Adhikary, S R; Fuller, S J; Varikatt, W; Sanderson-Smith, M L; Sluyter, V; Alexander, S I; Sluyter, R; Watson, D
Summary: Graft- versus -host disease (GVHD) remains a major problem after allogeneic haematopoietic stem cell transplantation, a curative therapy for haematological malignancies. Previous studies have demonstrated a role for the adenosine triphosphate (ATP)-gated P2X7 receptor channel in allogeneic mouse models of GVHD. In this study, injection of human peripheral blood mononuclear cells (PBMCs) into immunodeficient non-obese diabetic-severe combined immunodeficiency-interleukin (NOD-SCID-IL)-2Rγ null (NSG) mice established a humanized mouse model of GVHD. This model was used to study the effect of P2X7 blockade in this disease. From five weeks post-PBMC injection, humanized mice exhibited clinical signs and histopathology characteristic of GVHD. The P2X7 antagonist, Brilliant Blue G (BBG), blocked ATP-induced cation uptake into both murine and human cells in vitro . Injection of BBG (50 mg/kg) into NSG mice did not affect engraftment of human leucocytes (predominantly T cells), or the clinical score and survival of mice. In contrast, BBG injection reduced circulating human interferon (IFN)-γ significantly, which was produced by human CD4 + and CD8 + T cells. BBG also reduced human T cell infiltration and apoptosis in target organs of GVHD. In conclusion, the P2X7 antagonist BBG reduced circulating IFN-γ in a humanized mouse model of GVHD supporting a potential role for P2X7 to alter the pathology of this disease in humans. Graphical Abstract: